Implementasi Digital Marketing dalam Meningkatkan Strategi Pemasaran Produk UMKM di Kelurahan Mangunharjo Kota Semarang - Bahlawan, Zuhriyan Ash Shiddieqy; Megawati; Triwibowo, Bayu; Prasetiawan, Haniif; Prasojo, Dwi; Amrullah, Fauzan; Mayasari, Dyta Silvia (Journal of Industrial Community Empowerment, 2023)
Micro, Small and Medium Enterprises (MSMEs) in Indonesia are the largest business units that support the country's economy. In Mangunharjo District, Tugu District, Semarang City, there are several groups of MSMEs which are mainly engaged in the food processing industry. However, MSME owners face various challenges, such as a lack of marketing methods. As a result, many MSMEs only produce food products when there is an order and rely on consignment at the nearest shop for a limited period of time. This problem requires a solution that can overcome the concerns of MSME owners, one of which is by changing marketing methods. Currently, MSMEs in the regions only rely on traditional marketing methods. By holding training activities for the public about the benefits of digital marketing, it is hoped that MSME owners can change their perspective and adopt more modern marketing methods. Through evaluations carried out after training, the MSME group has started to utilize digital platforms to market their products. The results show that MSMEs are starting to get used to digital marketing to increase sales value.